Numerical Modelling of Post-Ground Subsystem in Road Safety Barrier Crash Tests - KLASZTORNY, Marian; NYCZ, Daniel Bronislaw; DZIEWULSKI, Pawel; GIELETA, Roman; STANKIEWICZ, Michal; ZIELONKA, Karol (Engineering Transactions, 2019)
A new analytical algorithm for determining the elastoplastic parameters for soft, medium and hard plastic cohesive soils, corresponding to *MAT_005_SOIL_AND_FOAM material model available LS-Dyna FE code, was formulated. The numerical modelling of the post-soil subsystem, applicable in the modelling of road safety barrier crash tests using this material model of the roadside dehydrated ground, was developed. The methodology was presented on the example of a Sigma-100 steel post partly driven into the soil and subjected to a static flexural-torsional test using a horizontal tensioned rope. The experimental validation of the numerical modelling and simulation was carried out on the testing site at the Automotive Industry Institute, Warsaw, Poland. The simulations were carried out for numerical models with soil solid elements with reduced integration (ELFORM_1) and full integration (ELFORM_2). The simulation results are in the form of graphs of the rope tension vs. displacement of the upper measurement point of the post and in the form of deformation of the post-soil system. It was shown that the validation experiment was carried out on the post embedded in hydrated soft plastic cohesive soil.